2019
DOI: 10.1172/jci98785
|View full text |Cite
|
Sign up to set email alerts
|

Targeting compensatory MEK/ERK activation increases JAK inhibitor efficacy in myeloproliferative neoplasms

Abstract: Constitutive JAK2 signaling is central to myeloproliferative neoplasm (MPN) pathogenesis and results in activation of STAT, PI3K/AKT, and MEK/ERK signaling. However, the therapeutic efficacy of current JAK2 inhibitors is limited. We investigated the role of MEK/ERK signaling in MPN cell survival in the setting of JAK inhibition. Type I and II JAK2 inhibition suppressed MEK/ERK activation in MPN cell lines in vitro, but not in Jak2V617F and MPLW515L mouse models in vivo. JAK2 inhibition ex vivo inhibited MEK/ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 80 publications
6
89
1
Order By: Relevance
“… 29 Recently, PDGFRα signaling was shown to remain active despite JAK2 inhibition in vivo and is a cell-intrinsic bypass for maintaining downstream ERK signaling upon ruxolitinib treatment. 30 To date, allogeneic stem cell transplantation is the only curative treatment for PMF; however, transplantation is only suitable for a subset of high-risk patients and limited by comorbidities and donor availability. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“… 29 Recently, PDGFRα signaling was shown to remain active despite JAK2 inhibition in vivo and is a cell-intrinsic bypass for maintaining downstream ERK signaling upon ruxolitinib treatment. 30 To date, allogeneic stem cell transplantation is the only curative treatment for PMF; however, transplantation is only suitable for a subset of high-risk patients and limited by comorbidities and donor availability. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that disease progression in MF patients treated with ruxolitinib is associated with activation of receptor tyrosine kinase and RAS pathway mutations, and RAS pathway mutations, including PTPN11 (which encodes the SHP2 phosphatase), confer poor prognosis [ 24 , 25 ]. Notably, inhibition of MEK, a mediator of MAP kinase signaling, has been shown to be effective in murine models as a single agent as well as in combination with ruxolitinib [ 175 ]. Similarly, SHP2 mediates activation of the RAS signaling pathway, and targeting SHP2 can synergize with ruxolitinib in preclinical models and may antagonize disease in a murine model of MPN [ 176 ].…”
Section: Novel Combinations Pending Clinical Experiencementioning
confidence: 99%
“…A recent MPN preclinical study showed that JAK2 inhibitors induce a strong reduction in STAT signaling but only marginally reduce MEK/ERK signaling. 19 Multiplexed analyses of 34 secreted factors in Jak2 V617F-mutant mice showed that transcript levels of the receptor Pdgfra, as well as the ligands Pdgfa and Pdgfb, were maintained in BM and spleen during ruxolitinib treatment. 19 Additional experiments showed that PDGF signaling through MEK/ERK was not reduced upon ruxolitinib treatment.…”
Section: Dual Targeting Of Jak and Jak/platelet-derived Growth Factormentioning
confidence: 99%
“…19 Multiplexed analyses of 34 secreted factors in Jak2 V617F-mutant mice showed that transcript levels of the receptor Pdgfra, as well as the ligands Pdgfa and Pdgfb, were maintained in BM and spleen during ruxolitinib treatment. 19 Additional experiments showed that PDGF signaling through MEK/ERK was not reduced upon ruxolitinib treatment. Combined treatment with JAK2 and MEK inhibitors was superior over inhibition with either compound alone in mouse models of Jak2 V617F and MPLW515-induced myelofibrosis, and reduced Pdgfra, Pdgfa, and Pdgfb transcript expression.…”
Section: Dual Targeting Of Jak and Jak/platelet-derived Growth Factormentioning
confidence: 99%